Polyurethane-functionalized starch nanocrystals as anti-tuberculosis drug carrier - Shivang K. Desai (Nature Portfolio, 2021)
Abstract Studies related to loading ability and delivery of clinically used first-line anti-tuberculosis drugs (ATDs) such as isoniazid, rifampicin, pyrazinamide and streptomycin on the surface of starch-derived bulk and nanopolyurethanes (SBPUs and SNPUs) as drug delivery systems (DDS) have been focused to minimise or remove the drug-associated adverse effects. The efficiencies of nanopolyurethanes obtained from the differently substituted cyclic aliphatic and aromatic isocyanates have been studied for drug loading and release purposes. Different advanced instrumental techniques analysed the structural and morphological properties, thermal stability and crystallinity of the starch nanopolyurethans. Average particle sizes ranging from 27.35–42.38 nm to 126.89–218.60 nm for starch nanopolyurethans, SNPU3i and SNPU4i, respectively, were determined by high-resolution transmission electron microscopy. Similarly, the loading efficiency of ATDs to the surfaces of SNPUs and SBPUs was observed in the range of 60–97% while ATDs-loaded SNPUs showed a sustainable release profile for all ATDs except for streptomycin. However, most SBPUs provided burst-release for all the above-mentioned ATDs in pH-dependent studies. The anti-tuberculosis assay against the Mycobacterium tuberculosis H37Rv strain revealed that streptomycin-loaded SNPU4i and isoniazid-loaded SNPU7i are approximately 42 and 7 times more active than the native streptomycin and isoniazid, respectively.